Influenza A virus-infected lung epithelial cell co-culture with human peripheral blood mononuclear cells - Loh, L; Koutsakos, M; Kedzierska, K; Hinks, T (Springer Verlag, 2019)
Sensing of influenza A virus (IAV) infection by pattern recognition receptors can occur by either direct infection of lung epithelial cells or uptake of virus-infected cells by innate cells such as dendritic cells/monocytes. This triggers a series of downstream events including activation of the inflammasome, the production of cytokines, chemokines, and the upregulation of stress-induced ligands that can lead to the activation of innate cells. These cells include innate lymphocytes such as MAIT, NKT, NK, and γδ T cells. Here we describe a method used to allow activation of human innate lymphocytes in co-culture with an IAV-infected human lung epithelial cell line (A549) to measure ex vivo effector functions (TNF and IFNγ) in a mixed culture environment. We describe (1) infection of the human lung epithelial cell line, (2) co-culture with PBMC, and (3) measurement of activation using intracellular cytokine staining.